2023
DOI: 10.1002/alz.12982
|View full text |Cite
|
Sign up to set email alerts
|

The association of MIND diet with cognitive resilience to neuropathologies

Abstract: IntroductionCognitive resilience (CR) can be defined as the continuum of better through worse than expected cognition, given the degree of neuropathology. The relation of healthy diet patterns to CR remains to be elucidated.MethodsUsing longitudinal cognitive data and post mortem neuropathology from 578 deceased older adults, we examined associations between the Mediterranean‐DASH Intervention for Neurodegenerative Delay (MIND) diet at baseline and two standardized CR measures reflecting higher cognitive level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…reported a significant negative correlation between green leafy vegetables and AD pathology. [ 15 ] A low‐fat diet or a modified Mediterranean ketogenic diet for 6 weeks can benefit adults with mild cognitive impairment. [ 16 ] González‐Domínguez et al revealed that the level of Trp from AD and mild cognitive impairment patients was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…reported a significant negative correlation between green leafy vegetables and AD pathology. [ 15 ] A low‐fat diet or a modified Mediterranean ketogenic diet for 6 weeks can benefit adults with mild cognitive impairment. [ 16 ] González‐Domínguez et al revealed that the level of Trp from AD and mild cognitive impairment patients was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Over a 9-year follow-up, the Rush Memory and Aging Project showed that adherence to the MIND diet was associated with higher cognitive levels and slower rates of cognitive decline, after controlling for neuropathology. Overall MIND score was more strongly related to cognitive outcomes than the individual food components [11]. Meta-analysis of cohorts showed that 1 SD increment of the MIND score was associated with 0.042 units higher in global cognitive function z score and 0.010 units slower in annual cognitive decline [12 ▪ ].…”
Section: Diet and Cognitionmentioning
confidence: 99%
“…It prioritizes plants, nuts, berries, fish, and olive oil, all known for their potential cognitive benefits. [ 21 , 22 , 23 ] Research increasingly suggests that specific diets and nutrients may delay Alzheimer's‐related cognitive decline. [ 24 , 25 ] However, the complex mechanisms of the brain that are affected remain unclear.…”
Section: Introductionmentioning
confidence: 99%